Exploration of the Tumor-Suppressive Immune Microenvironment by Integrated Analysis in EGFR-Mutant Lung Adenocarcinoma - Li, Teng; Pang, Xiaocong; Wang, Junyun; Wang, Shouzheng; Guo, Yiying; He, Ning; Xing, Puyuan; Li, Junling (Frontiers in Oncology, 2021)
Background Clinical evidence has shown that few non-small cell lung cancer (NSCLC) patients with epidermal growth factor receptor (EGFR) mutations can benefit from immunotherapy. The tumor immune microenvironment (TIME) is a significant factor affecting the efficacy of immunotherapy. However, the TIME transformational process in EGFR-mutation patients is unknown. Methods The mRNA expression and mutation data and lung adenocarcinoma (LUAD) clinical data were obtained from The Cancer Genome Atlas (TCGA) database. Profiles describing the immune landscape of patients with EGFR mutations were characterized by differences in tumor mutation burden (TMB), ESTIMATE, CIBERSORT, and microenvironment cell populations-counter (MCP-counter). Results In total, the TCGA data for 585 patients were analyzed. Among these patients, 98 had EGFR mutations. The TMB was lower in the EGFR group (3.94 mut/Mb) than in the KRAS mutation group (6.09 mut/Mb, P < 0.001) and the entire LUAD (6.58 mut/Mb, P < 0.001). The EGFR group had a lower population of activated immune cells and an even higher score of immunosuppressive cells. A further inter-group comparison showed that differences in the TMB and tumor-infiltrating lymphocytes were only found between patients with oncogenic mutations and unknown mutation. Meanwhile, there were more myeloid dendritic cells (DCs) in EGFR 19del than in L858R-mutation patients and in common mutation patents than in uncommon mutation patients (P < 0.05). Additionally, we established a D score, where D = MCP-counter score for cytotoxic T lymphocytes (CTLs) / MCP-counter score for myeloid DCs. Further analysis revealed that lower D scores indicated immune suppression and were negatively related to several immunotherapy biomarkers. Conclusions The TIME of EGFR mutant NSCLC was immunosuppressive. Myeloid DCs gradually increased in EGFR 19del, L858R, and uncommon mutations. The potential role of CTLs and DCs in the TIME of patients requires further investigation.